Nonlinear viscoelastic model for asphalt mixture subjected to repeated loading. Issue 4 (1st October 2016) - Pei, Jianzhong; Fan, Zepeng; Liu, Huanjiao; Zhang, Jiupeng; Li, Rui; Li, Yanwei
Abstract : The modified Burgers model was selected to develop the nonlinear viscoelastic (NLVE) model of asphalt mixture subjected to repeated load, and the permanent strain was expressed as the summation of residual viscoelastic (RVE) and nonlinear viscous (NLV) strains. It is found that RVE and NLV strains increase with the increasing loading cycles, but RVE strain decreases with the increasing rest period while NLV is not related to the rest period. The proportion of NLV strain to total strain increases with the rest period and loading cycles and the NLV strain is the predominant part if the rest period is long enough. Thus, the NLVE model could be predigested. The repeated load permanent deformation tests of three asphalt mixtures were conducted at different temperatures and stresses for model validation and parameter analysis. It is found that the permanent strain increases with test temperature and stress and the proposed NLVE model can well describe the mechanical behaviour of the asphalt mixture subjected to repeated load. Moreover, fitting results show that the modified Burgers model parameters, and decrease with test temperature but increase with stress while parameter shows no significant change rule.